Negative Symptoms and Reward Disturbances in Schizophrenia Before and After Antipsychotic Monotherapy. (January 2018) - Nielsen, Mette Ødegaard; Rostrup, Egill; Broberg, Brian Villumsen; Wulff, Sanne; Glenthøj, Birte
Background . Negative symptoms (NS) are a central part of the symptomatology of schizophrenia, which is highly correlated to the functional outcome. Disturbances of the brain reward system are suggested to be central in the pathogenesis of NS by decreasing motivation and hedonic experiences. In this study, we compared reward-related brain activity in patients improving and not improving in NS after treatment with amisulpride. Methods . Thirty-nine antipsychotic-naive patients and 49 healthy controls completed functional magnetic resonance imaging with a modified monetary incentive delay task. Psychopathology of the patients was characterised with Positive and Negative Syndrome Scale (PANSS), and they were treated with individual doses of amisulpride (mean 271 mg) for 6 weeks, after which the examinations were repeated. Results . Patients improved on positive, general, and total PANSS score after treatment ( P < .001). Fourteen patients had ≥20% improvement of NS, whereas 25 patients improved <20%. At baseline, one-way analysis of variance showed group difference bilaterally in the caudate nucleus and in the right nucleus accumbens (all P < .002), which was caused by decreased reward anticipation activity in the nonimproving patients compared to healthy controls. There was a significant group × time interaction, with the healthy controls and the improvers decreasing and the nonimprovers increasing in reward anticipation activity after treatment, most pronounced in the left caudate nucleus ( P = .001). Discussion . Patients improving in NS score had a less aberrant reward system at baseline, but reward related activity was reduced over time. Patients not improving in NS showed decreased striatal reward-activity at baseline, which improved over time. Whether this is associated with alteration in working memory and reward learning or with pronounced symptoms within specific domains of NS may be addressed in future studies.